Prevalence Of Alcohol Consumption In First-Year Romanian Medical Students And Its Association With Cardiovascular Risk Factors - Adriana Gherbon; Romulus Timar; Mirela Frandes; Marioara Nicula; Dorel Dronca; Mirela Ahmadi (European Scientific Journal, ESJ, 2021)
Alcohol is the third risk factor for premature disease and death for the general population of the European Union (EU) after smoking and high blood pressure. In the case of young people, they consume alcohol based on the desire to explore, sometimes associating it with recreational drugs use, thus increasing the risk of negative consequences. The objective of this study was to assess the prevalence of alcohol consumption and its association with other cardiovascular risk factors in first-year medical students. The studied lot consisted of 434 first-year medical students, 30.18% boys, and 69.82% girls, with the mean age of 19.48 ± 0.53 years. The methods included the administration of a questionnaire (CORT 2004 questionnaire on health risk behaviors in first-year medical students) for assessing both alcohol consumption and stress state, as well as blood pressure determination, and anthropometric parameters. The prevalence of alcohol consumption among first-year medical students was 22.58%, with a net prevalence of male gender (57.25% M versus 7.59% F) (p <0.001, X2 = 129.02). The main reasons for alcohol consumption were the festive and official occasions and the desire to integrate into the group. People with whom they prefer to drink alcohol were friends, colleagues, and family. The age at which most people began to consume alcohol was 13-14 years old, and the favorite drink was beer among boys and wine among the girls. Regarding the cardiovascular risk factors, positive correlations were obtained between alcohol and smoking, increased consumption of bread, sedentary lifestyle, and increased body mass index. Students need to be educated from the first year of study on the long-term consequences of alcohol consumption related to the development of the cardiovascular disease, and further studies are needed to see if educational programs really reduce the prevalence of alcohol consumption.